Virginia women. their lives and times - Kierner, Cynthia A., 1958- (Southern women (Athens, Ga.), 2016)
The exploration of the history of Virginia women through the lives of exemplary and remarkable individuals. Seventeen essays written by established and emerging scholars recover the stories and voices of a diverse group of women.